Accent Bias and Perceptions of Professional Competence in England. (December 2021) - Levon, Erez; Sharma, Devyani; Watt, Dominic J. L.; Cardoso, Amanda; Ye, Yang
Unequal outcomes in professional hiring for individuals from less privileged backgrounds have been widely reported in England. Although accent is one of the most salient signals of such a background, its role in unequal professional outcomes remains underexamined. This paper reports on a large-scale study of contemporary attitudes to accents in England. A large representative sample ( N = 848) of the population in England judged the interview performance and perceived hirability of "candidates" for a trainee solicitor position at a corporate law firm. Candidates were native speakers of one of five English accents stratified by region, ethnicity, and class. The results suggest persistent patterns of bias against certain accents in England, particularly Southern working-class varieties, though moderated by factors such as listener age, content of speech, and listeners' psychological predispositions. We discuss the role that the observed bias may play in perpetuating social inequality in England and encourage further research on the relationship between accent and social mobility.